2021
DOI: 10.5603/arm.a2021.0114
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19—Deliberating beyond Steroids in 2021

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A recent systematic review of 150 studies with 33,805 patients showed that COVID-19 increased the risk of developing MACE. These complications were more frequently documented in patients with pre-existing cardiovascular comorbidities and disease severity [ 46 ]. However, a recent report by Xie et al .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of 150 studies with 33,805 patients showed that COVID-19 increased the risk of developing MACE. These complications were more frequently documented in patients with pre-existing cardiovascular comorbidities and disease severity [ 46 ]. However, a recent report by Xie et al .…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, COVID-19 spread across the globe in pandemic proportions and caused huge morbidity and mortality. The sudden spurt in cases led to widespread fear, exhaustion of health-care resources and multiple treatment regimens in India 7 ; evidence-based treatment approach for treatment could hardly be realised. However, till evidence for efficacy and safety is generated, indiscriminate use of any drug should be discouraged.…”
mentioning
confidence: 99%